Strategi Internalisasi Nilai-Nilai Keagamaan Melalui Matapelajaran Akidah Akhlak Dalam Pembentukan Karakter Kedisiplinan Siswa di MI NW Anjani - Hilman (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Amin, 2026)
Education is not only aimed at developing students’ intellectual intelligence but also at shaping their character. In practice, Indonesia still faces various moral problems, such as increasing deviant behaviors, violations of school rules, low discipline, and declining politeness among students. Previous studies have emphasized the importance of character education based on religious values; however, few studies have specifically examined the strategies used by teachers to internalize religious values in shaping students’ disciplinary character. This gap becomes the focus of the present study. This study employed a qualitative descriptive case study method with a field research approach conducted at Madrasah Ibtidaiyah Nahdlatul Wathan (MI NW) Anjani. Data were collected through participant observation, structured interviews, and documentation, while data analysis followed Miles and Huberman’s model, including data reduction, data display, and conclusion drawing. The findings indicate that Akidah Akhlak teachers implement strategies for internalizing religious values through several approaches, including habit formation, exemplary behavior, embedding values in lesson materials, positive reinforcement and rewards, as well as corrective guidance and educational sanctions. Supporting factors for the success of these strategies include the active role of teachers as role models, curricula that integrate religious values, a religious school environment, and collaboration with parents. In contrast, limiting factors include insufficient facilities and infrastructure and lack of parental support. In conclusion, the internalization of religious values through Akidah Akhlak lessons effectively shapes students’ disciplinary character, provided it is supported by exemplary teachers, a conducive school environment, and parental involvement. The implications of this study emphasize the importance of a holistic approach to character education, combining academic learning with religious values consistently both at school and at home.